TYPE OF HEARING LOSS AMONG CHRONIC SUPPURATIVE OTITIS MEDIA PATIENTS - Mehwish; Sultan, Hadia; Asfura Badar, Syeda; Shanawar, Minahil; Tahir, Fatima; Mukhtar, Faiza; Batool, Sehar (Journal of Postgraduate Medical Institute, 2024)
Objective: This study aims to explore the type and severity of hearing loss in patients with chronic suppurative otitis media. Methodology: This cross-sectional study with non-probability purposive sampling technique was carried out at The Children Hospital and The Institute of Child Health (CHICH) and Mayo Hospital Lahore, Duration was 6 months (May 2023 to October 2023). Sample size was 145 CSOM patients of both gender (male, female) with ages 5 to 40 years were included. Patient with CSOM with any comorbid factors were excluded. A pre-design performa and pure tone audiometry were used. Data was analysed through SPSS version 23.0 package. Results: Out of 145 patients, 62 (42.8%) male and 83 (57.2%) female patients. Most patients 37 (25.5%) were in age group 10 to 15 years. 105 (72.4%) patients had earache and drainage in their ears. Patients with tubo-tympanic type perforation were 119 (82.1%) and with attico-antral type perforation were 26 (17.9%). Conductive hearing loss 103 (71%) was the most prevalent type with moderate degree 63 (61.2%) whereas, sensorineural hearing loss was 15 (10.3%) from which mostly had moderately severe degree 5 (33.3%), and mixed hearing loss was 27 (18.6%) with mostly patients had moderately severe degree 18 (66.7%). Conclusion: Conductive hearing loss was the most prevalent type with majority have moderate degree. Patients with tubo-tympanic perforation is more common than attico-antral. Whereas, sensorineural hearing loss and mixed hearing loss is also seen in these patients.